2017
DOI: 10.21059/buletinpeternak.v41i4.22052
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Performances of Sumba Ongole Cows Inseminated With Frozen Belgian Blue Semen

Abstract: INTISARITujuan dari penelitian ini adalah untuk mengetahui kinerja reproduksi dari sapi betina Sumba Ongole (SO) yang diinseminasi buatan (IB) dengan semen beku Belgian Blue (BB). Penelitian ini diharapkan dapat digunakan sebagai acuan dalam pemeliharaan sapi betina khususnya dalam pelaksanaan IB, serta hasil penelitian ini juga dapat digunakan sebagai bahan untuk rujukan atau acuan penelitian-penelitian selanjutnya. Parameter penelitian meliputi tanda-tanda gejala berahi, service per conception ratio (S/C rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
2
3
0
Order By: Relevance
“…The calves' withers height in this study is not in agreement with the paper from Buchanan and Lenstra (2015), which mentioned that Wagyu cattle have small to medium body frames; whereas BX and Belgian Blue have medium to large body frames. The body measurements of BBcrossed and Wagyu-crossed in this study are similar to those of calves from Sumba Ongole dams inseminated with BB semen; their wither height, body length, and heart girth were 68.33±4.57; 64.66±4.16 and 71.68±1.54 cm respectively (Aji et al, 2017). Recent results obtained in Brazil in the state of Goyas indicate the birth weight of Belgian Blue x Zebu Nelore crosses is on average 41.1 Kg.…”
Section: Pre-weaning Growthsupporting
confidence: 80%
See 3 more Smart Citations
“…The calves' withers height in this study is not in agreement with the paper from Buchanan and Lenstra (2015), which mentioned that Wagyu cattle have small to medium body frames; whereas BX and Belgian Blue have medium to large body frames. The body measurements of BBcrossed and Wagyu-crossed in this study are similar to those of calves from Sumba Ongole dams inseminated with BB semen; their wither height, body length, and heart girth were 68.33±4.57; 64.66±4.16 and 71.68±1.54 cm respectively (Aji et al, 2017). Recent results obtained in Brazil in the state of Goyas indicate the birth weight of Belgian Blue x Zebu Nelore crosses is on average 41.1 Kg.…”
Section: Pre-weaning Growthsupporting
confidence: 80%
“…The birth weight of BB-crossed calves in this study was considerably similar to the crossbred calves between Belgian Blue sires and Sumba Ongole (SO) dams, which was 31.33±4.93 kg (Aji et al, 2017) because the effect of the mutation in the myostatin gene in Belgian Blue (Charlier et al, 1995). Arthur (1995) reported that the birth weight of double-muscled cattle crossed with conventional cattle was 26.9-34.7 kg; whereas calves from both double-muscled parents were 31.9-42.2 kg.…”
Section: Birth Weightsupporting
confidence: 65%
See 2 more Smart Citations
“…Belgian Blue (BB) is one of the cattle originating from Belgium. The advantage of Belgian Blue cattle compared to other European cattle is that Belgian Blue cows have double muscle or double muscular producing genes (Aji et al, 2017). Belgian Blue cattle has a unique phenotype of "double muscle" due to the deletion of 11 bases in exon three of the myostatin gene (Agung et al, 2016).…”
Section: Introductionmentioning
confidence: 99%